The environmental control of development in winter wheat - Baker, C.K. (1979)
1. The relevance of studies of development in crop-weather investigations is reviewed and the aims of the present work are outlined. 2. The procedures used in studying development in field crops of winter wheat are described. The developmental progress of the plants was ascertained by frequent dissections. 3. Primordium initiation at the stem apex is strongly dependent upon apex temperature, which could be accurately estimated from standard meteorological screen temperatures. Like numerous other complex biological processes, initiation has a markedly linear response to temperature: the number of primordia initiated is therefore in direct proportion to accumulated temperature (thermal time). To calculate this requires estimation of the base temperature (Tb). 4. The linear dependence upon temperature of the initiation rates of leaves, spikelets and florets (R1, Rs and Rf ) was evident. Spikelets were initiated faster than leaves ; rate changed at a distinct inflexion point, usually at about the end of leaf initiation but sometimes later. Tb = 0 grad. C for leaves but was higher for spikelets and florets. The shift in Tb apparent17 occurred because Rs and Rf were strongly influenced by the day length at inflexion point. When temperature was corrected for day length influence, Tb = 0°0 for each developmental phase. Inflexion point timing apparently depended upon interaction between vernalisation before crop emergence and photo thermal time afterwards. 5. Leaf appearance rate in thermal time was linear but apparently influenced by the direction and magnitude of day length change at emergence, with a possible secondary effect of current day length. Leaf extension was strongly related to temperature. The gradient of lamina size up the stem appeared to be ontogenetically determined. 6. Compared with early-sown or fully-fertilised crops, floret survival and grain yield was lower in those sown late or inadequately fertilised, probably on account of their smaller amount of growth per unit of developmental time.